The Effectiveness of Early Grade Reading Assessment (EGRA) Method on Elementary Students’ Reading Fluency - Daeli, Griselda Artha; Dewi, Fransisca Iriani Roesmala (Indonesian Journal of Social Research (IJSR), 2024)
Along with the evolution of time, individuals were required to learn quickly, especially in mastering new things. Therefore, it became the main reason reading is considered a fundamental skill that should be mastered from a young age. Several methods have been created to enhance reading fluency, including the Early Grade Reading Assessment (EGRA). This research aims to determine the EGRA method's effectiveness on students' reading fluency. A quantitative approach with a quasi-experimental method and a nonrandomized pretest-posttest control group design was employed. Thirty-seven fourth-grade elementary school students at SDN X Cikarang Regency participated. Eight (8) elements of EGRA were used as treatment materials, namely: (a) letter identification; (b) distinguishing initial sound; (c) nonword reading; (d) read aloud/oral reading; (e) reading comprehension; (f) listening comprehension; (g) Indonesian vocabulary; and (h) dictation. As for analyzing the data, the researcher employed Mann-Whitney U to compare the pretest and posttest scores of the control and experimental groups. The results showed that The EGRA method significantly improved reading fluency in fourth-grade elementary school students (p < 0.05). Thus, the EGRA method can help educators teach elementary school students to read more fluently.